Pseudomonas Infection Affects the Growth and Development of Aphis gossypii by Disrupting Energy Metabolism and Reproductive Processes - Qiqing Yu; Ruichang Niu; Xueke Gao; Junyu Luo; Jinjie Cui; Li Wang; Xiangzhen Zhu (Insects)
For instance, Pseudomonas is involved in numerous life processes of A. gossypii and exerts a significant influence on its physiological indicators. The results demonstrate that Pseudomonas infection disturbs the normal growth and development of A. gossypii, resulting in a substantial reduction in the number of offspring. Compared with the uninfected control group, the innate rate of increase and the endogenous growth rate are markedly lower. Moreover, RNA-sequencing revealed that genes related to energy synthesis and nutrient metabolism were significantly upregulated in A. gossypii infected with Pseudomonas. Simultaneously, the infection led to a significant downregulation of genes related to alkaline phosphatase in the folate-synthesis pathway and histone proteinase B synthesis in the metabolism pathway of A. gossypii. These experimental findings indicate that Pseudomonas infection disrupts the growth and development of A. gossypii, specifically manifested as a significant upregulation of genes related to energy synthesis and nutrient metabolism and a downregulation of genes related to reproduction. Overall, these results offer support for the study of the interactions between aphids and symbiotic bacteria.